2013
DOI: 10.1007/s00586-012-2603-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical procedure and initial radiographic results of a new augmentation technique for vertebral compression fractures

Abstract: Purpose Recently, a new minimally invasive technique called 'vertebral body stenting' (VBS) was introduced for the treatment of osteoporotic vertebral fractures. The technique was developed to prevent the loss of reduction after deflation of the balloon and to reduce the complication rate associated with cement leakage. Methods The amount of kyphosis correction, improvement of vertebral body height and quantitative cement leakage rate by applying CT-based quantitative volumetry after VBS were measured in 27 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 29 publications
2
40
3
Order By: Relevance
“…Thaler et al reported a 25.5% extrusion rate in their VBS series and Werner et al had a 20% minor and 10% major leakage rate. In both studies, a viscometer was used [12,13]. The final rate of symptomatic extrusions in our series was 1% which is lower than the 2.6% in VP and comparable with the 1.3% in BKP reported by Hulme [2].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Thaler et al reported a 25.5% extrusion rate in their VBS series and Werner et al had a 20% minor and 10% major leakage rate. In both studies, a viscometer was used [12,13]. The final rate of symptomatic extrusions in our series was 1% which is lower than the 2.6% in VP and comparable with the 1.3% in BKP reported by Hulme [2].…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, stratified results by fracture type were not reported, which may have revealed differences between the two therapies. Thaler et al could only achieve an average 3.5° reduction of vertebral kyphosis in 27 patients, but the mean preoperative Beck Index of 0.87 implies a smaller reduction potential than that of our group (preop 0.73), which may explain the better reduction of 4.2° in the current study [12]. …”
Section: Discussioncontrasting
confidence: 67%
“…[15][16][17] It is widely used in osteoporotic vertebral compression fractures, with numerous studies showing its effectiveness as a form of pain control and preventing further vertebral collapse. [1][2][3][4]8,11,18,19 Studies showed that it provides nearly immediate pain relief in over 80% of cases, thus allowing patients to mobilize postoperatively. 2,3,20 From 2009 to 2010, 3 randomized controlled trials concluded that there was no superiority of vertebroplasty over nonsurgical management, or over a sham procedure.…”
Section: Discussionmentioning
confidence: 98%
“…40 Narcotics are occasionally required for pain, and calcitonin may provide relief in the acute phase. 42 Preventive treatments for osteoporosis play an increasing role in reducing the number of vertebral fractures in postmenopausal women and the elderly. 38 Vertebroplasty is a technique involving injecting polymethylmethacrylate into a fractured vertebral body; compared to conservative treatment, it shows greater pain relief, functional recovery, and health-related quality of life.…”
Section: Osteoporosismentioning
confidence: 99%